Hatching baby ostriches - Unknown:::Creator::::::::::::
Photograph shows baby ostriches hatching from their eggs along with eggs waiting to hatch. Behind the eggs is a fence separating the hatchlings from some adult ostriches. Photograph possibly taken at Alum Rock in San Jose, California.